Tautomeric Equilibrium Among the Derivatives of Benzoyl Vinegar Aldehydes - Ergashov Mansur Yarashovich; Savriyeva Nigina Qahramon qizi; Amonov Muhammad Murod o‘g‘li (Zien Journals, 2022)
In this work, using modern physicochemical research methods, the interaction of various amino acid solutions with the Cu(II) ion, the structure and properties of the resulting complex compounds were studied. The influence of the environment on the formation of pure and mixed ligand complexes from various obtained amino acids and the constants of stability and instability were determined.
Keywords: amino acid; 2-aminobutanedicarboxylic acid; thermal analysis; thermal stability